325 Exploring the Complexity of Dementia and Loneliness in Ireland. (16th September 2019) - Hartigan, Irene; Cornally, Nicola; Foley, Tony; Timmons, Suzanne; Park, Gyunghee; Jennings, Aisling; Müller, Nicole
Abstract: Background: Dementia and loneliness are both complex phenomenon's that impact on both mental and physical health. Research has identified that loneliness can increase a person's risk of mortality as much as smoking or alcohol consumption. People with dementia are at particular risk of loneliness and social isolation. This can negatively impact on a person with dementia's health. To effectively address loneliness in dementia, we must first understand how people with dementia experience loneliness. Methods: Interviews were conducted with people living with dementia. Participants comprised of eight community-dwelling individuals, aged 55 years and older (mean = 63.8; range = 55-77), who were each diagnosed with dementia at least one year prior to interview (range = 1.16 – >5 years). Interviews were conducted in participants' homes using a semi-structured format and lasted between 37-74 minutes. Results: Three key themes emerged: the importance of maintaining meaningful relationships, maintaining independence and socio-cultural influences on individual perceptions of loneliness and dementia. The results emphasise the importance of maintaining both a sense of self and meaningful relationships with others post-diagnosis for individuals who identified themselves as "not lonely". People living with dementia reported that the maintenance of social connection aids in fostering a sense of self-worth and self-management, which in turn mitigates feelings of loneliness. The majority of participants existing social connections with others was established prior to their diagnosis, although the maintenance of these relationships may have required an adjustment of their premorbid routines and method of social engagement. Conclusion: Human contact and a meaningful relationship are superior in preventing loneliness. Individual feelings of loneliness or lack thereof are not directly correlated to the coping mechanisms most commonly employed by individuals with dementia. Further exploration is need to understand how people with dementia, who live at home, perceive or experience loneliness.